SURVEY KUALITAS PELAYANAN BPJS KESEHATAN TERHADAP PETAMBAK BUDIDAYA UDANG DI KABUPATEN INDRAMAYU - Robidi; Maolani, Rukaesih A.; Sapolo, Supriyadi (Premium Insurance Business Journal, 2020)
As we have known, that now shrimp is an export commodities that fairly developing from year to year, so that the Marine and Fisheries sector is one of the sourches of national economic growth. Accordingly, shrimp farmer cultivation are the assets whose needed by us to improve the economy in the fisheries sector. Therefore, it is appropriate they get concern from Government for preserve the health of the farmer cultivation and their families. The research conducted aim for known: (1) The level of quality of Health’s BPJS Insurance services for patients of shrimp farmer cultivation and their families, (2) To find out what the difficulties directly experienced by farmers when they came to seek treatment at both the Health Center and the Hospital. The research carried out in the Karangsong Village, Indramayu District, West Java Province to shrimp farmer cultivation within survey methods. The concluded of final research is shrimp farmers cultivation still didn’t satisfied with services officers in Health Center and Hospital. Another also, difficulties are the distance of shrimp farmer cultivation’s residence so far from Health Center and Hospital when they desire to get treatment of there and long in service because amount of some doctors on duty there.